La reforma fiscal del 2014 y su efecto en las políticas de dividendos: Evidencia de la Bolsa Mexicana de Valores - César Corona Pacheco; Gustavo Vaca Medina; Jesús Vaca Medina (Atlantic Review of Economics (ARoEc), 2024)
– The main objective of this research work is to analyze the impact that the 2014 Tax Reform in Mexico has had on the value of the company, on cash flows, and payment of dividends of companies listed on the BMV, taking take into account their dividend polici es. The study has been carried out using a balanced panel data model with fixed effects and with the help of STATA 12, the interaction of the reform and the payment of dividends (RPD), reveals negative results, in the same magnitude as the total effect of dividends in the share price (SHPipc), in addition to the (ROE) return on equity, (L.TAXSH) and taxes per share show negative results. The study shows the relationship that exists between dividend policies and the tax reform, providing evidence on what hap pens in the Mexican stock market, the limitations are the use of a single econometric model and the low number of stations analyzed, it is relevant because there are few studies of the Mexican case.
Keywords: G4; G3; H2; M4; 330; Corporate governance; Dividend policy; Taxes per share; Tax reform